Prophetic Ethics of Inclusion and Conflict Resolution: A Neo-Traditionalist Interpretation of the Sirah - Nabi, Danish; Parray, Tauseef Ahmad (Jurnal Theologia, 2025)
In an era marked by escalating religious intolerance and social fragmentation, the ethical legacy of the Prophet Muhammad (Sirah) offers a compelling yet underexplored framework for promoting peaceful coexistence. Despite its rich content, contemporary discourse often marginalises the inclusive and reconciliatory dimensions of the Prophet’s life. This study aims to examine how neo-traditionalist Muslim scholars—particularly from the West and the Indian subcontinent—interpret the Sirah to address issues of social inclusiveness and conflict resolution. Employing a qualitative descriptive method, this research integrates content analysis, thematic exploration, and comparative interpretation. It focuses on key historical events such as Hilf al-Fudul, the Constitution of Medina, the migration to Abyssinia, the Treaty of Hudaybiyyah, and the Conquest of Makkah. The findings show that neo-traditionalist scholars present a contextual and ethical reading of the Sirah that aligns classical Islamic values with modern challenges. This study contributes to the growing field of peace studies in Islam by reviving the Prophet’s ethical model as a viable framework for interfaith harmony, minority rights, and conflict transformation in pluralistic societies.